Monitoring in adaptive co-management: Toward a learning based approach - Cundill, Georgina; Fabricius, Christo (Journal of Environmental Management, 2009)
The recognition of complexity and uncertainty in natural resource management has lead to the development of a wealth of conceptual frameworks aimed at integrated assessment and complex systems monitoring. Relatively less attention has however been given to methodological approaches that might facilitate learning as part of the monitoring process. This paper reviews the monitoring literature relevant to adaptive co-management, with a focus on the synergies between existing monitoring frameworks, collaborative monitoring approaches and social learning. The paper discusses the role of monitoring in environmental management in general, and the challenges posed by scale and complexity when monitoring in adaptive co-management. Existing conceptual frameworks for monitoring relevant to adaptive co-management are reviewed, as are lessons from experiences with collaborative monitoring. The paper concludes by offering a methodological approach to monitoring that actively seeks to engender reflexive learning as a means to deal with uncertainty in natural resource management.
Keywords: Adaptive co-management; Collaborative monitoring; Complexity; Social learning

The Adaptive Management System for the Tasmanian Wilderness World Heritage Area — Linking Management Planning with Effectiveness Evaluation - Jones, Glenys (Adaptive Environmental Management, 2009)
This paper provides a 30 year retrospective on the development of the adaptive management system for the Tasmanian Wilderness World Heritage Area (Australia). It describes the historical background, key influences and stages that paved the way to establishment of adaptive management. It outlines how effectiveness monitoring, evaluation and reporting are integrated with the management plan for the Area to establish an ongoing adaptive management cycle. The chapter presents figures and tools for adaptive management, including 5 useful questions for guiding the integration of effectiveness monitoring, evaluation and reporting into management plans and programs. Strengths and weaknesses of the adaptive management system are discussed. Key lessons and insights distilled from this experience are offered, including the importance of planned monitoring of management effectiveness; the role of stakeholder assessments; and the factors that can assist in sustaining longterm strategic programs despite ongoing institutional change. The chapter concludes with suggestions for fostering an enabling environment for adaptive management.
Keywords: Adaptive Management; Management Intent; Reserve Management; World Heritage

Agile Project Management: Creating Innovative Products - Highsmith, Jim (Addison Wesley, 2009)
Best practices for managing projects in agile environments―now updated with new techniques for larger projectsToday, the pace of project management moves faster. Project management needs to become more flexible and far more responsive to customers. Using Agile Project Management (APM), project managers can achieve all these goals without compromising value, quality, or business discipline. In Agile Project Management, Second Edition, renowned agile pioneer Jim Highsmith thoroughly updates his classic guide to APM, extending and refining it to support even the largest projects and organizations.  Writing for project leaders, managers, and executives at all levels, Highsmith integrates the best project management, product management, and software development practices into an overall framework designed to support unprecedented speed and mobility. The many topics added in this new edition include incorporating agile values, scaling agile projects, release planning, portfolio governance, and enhancing organizational agility. Project and business leaders will especially appreciate Highsmith’s new coverage of promoting agility through performance measurements based on value, quality, and constraints. This edition’s coverage includes: Understanding the agile revolution’s impact on product development Recognizing when agile methods will work in project management, and when they won’t Setting realistic business objectives for Agile Project Management Promoting agile values and principles across the organizationUtilizing a proven Agile Enterprise Framework that encompasses governance, project and iteration management, and technical practicesOptimizing all five stages of the agile project: Envision, Speculate, Explore, Adapt, and CloseOrganizational and product-related processes for scaling agile to the largest projects and teamsAgile project governance solutions for executives and management  The “Agile Triangle”: measuring performance in ways that encourage agility instead of discouraging itThe changing role of the agile project leader

A conceptual framework for analysing adaptive capacity and multi-level learning processes in resource governance regimes - Pahl-Wostl, Claudia (Global Environmental Change, 2009)
Governance failures are at the origin of many resource management problems. In particular climate change and the concomitant increase of extreme weather events has exposed the inability of current governance regimes to deal with present and future challenges. Still our knowledge about resource governance regimes and how they change is quite limited. This paper develops a conceptual framework addressing the dynamics and adaptive capacity of resource governance regimes as multi-level learning processes. The influence of formal and informal institutions, the role of state and non-state actors, the nature of multi-level interactions and the relative importance of bureaucratic hierarchies, markets and networks are identified as major structural characteristics of governance regimes. Change is conceptualized as social and societal learning that proceeds in a stepwise fashion moving from single to double to triple loop learning. Informal networks are considered to play a crucial role in such learning processes. The framework supports flexible and context sensitive analysis without being case study specific. First empirical evidence from water governance supports the assumptions made on the dynamics of governance regimes and the usefulness of the chosen approach. More complex and diverse governance regimes have a higher adaptive capacity. However, it is still an open question how to overcome the state of single-loop learning that seem to characterize many attempts to adapt to climate change. Only further development and application of shared conceptual frameworks taking into account the real complexity of governance regimes can generate the knowledge base needed to advance current understanding to a state that allows giving meaningful policy advice.
Keywords: Adaptive capacity; Adaptive governance; Climate change adaptation; Complexity; Institutions; Resource management; Social learning

Creating adaptive policies: a guide for policymaking in an uncertain world - Swanson, Darren; Bhadwal, Suruchi (IDRC, 2009)
Keywords: Adaptive natural resource management; Environmental policy; Government policy; Sustainable development

Adaptive monitoring: a new paradigm for long-term research and monitoring - Lindenmayer, David B.; Likens, Gene E. (Trends in Ecology & Evolution, 2009)
Long-term research and monitoring can provide important ecological insights and are crucial for the improved management of ecosystems and natural resources. However, many long-term research and monitoring programs are either ineffective or fail completely owing to poor planning and/or lack of focus. Here we propose the paradigm of adaptive monitoring, which aims to resolve many of the problems that have undermined previous attempts to establish long-term research and monitoring. This paradigm is driven by tractable questions, rigorous statistical design at the outset, a conceptual model of the ecosystem or other entity being examined and a human need to know about ecosystem change. An adaptive monitoring framework enables monitoring programs to evolve iteratively as new information emerges and research questions change.

Jumping off Arnstein's ladder: social learning as a new policy paradigm for climate change adaptation - Collins, Kevin; Ison, Ray (Environmental Policy and Governance, 2009)
Participation of citizens, groups, organizations and businesses is now an essential element to tackle climate change effectively at international, European Union, national and local levels. However, beyond the general imperative to participate, major policy bodies offer little guidance on what this entails. We suggest that the dominance of Arnstein's ladder of citizen participation in policy discourses constrains the ways we think about, and critically the purposes we ascribe to, participation in a climate change context. We suggest an alternative framing of climate change, where no single group has clear access to understanding the issue and its resolution. Thus adaptation is fundamentally dependent on new forms of learning. Drawing on experiences of social learning approaches to natural resource managing, we explore how a commitment to social learning more accurately embodies the new kinds of role, relationship, practice and sense of purpose required to progress adaptive climate change agendas and practices. Copyright © 2009 John Wiley & Sons, Ltd and ERP Environment.
Keywords: Arnstein's ladder; Climate change; Co-evolutionary adaptation; Natural resource management; Participation; Social learning

Glossary of Key Terms in Evaluation and Results Based Management - OECD (OECD, 2009)

The road to results: designing and conducting effective development evaluations - Imas, Morra; G, Linda; Rist, Ray C. (The World Bank, 2009)
The analytical, conceptual, and political framework of development is changing dramatically. The new development agenda calls for broader understandings of sectors, countries, development strategies, and policies. It emphasizes learning and continuous feedback at all phases of the development cycle. As the development agenda grows in scope and complexity, development evaluation follows suit. Development evaluator are moving away from traditional implementation and output-focused evaluation models toward results-based evaluation models, as the development community calls for results and embraces the millennium development goals. As the development community shifts its focus away from projects in order to comprehensively address country challenges, development evaluators are seeking methods with which to assess results at the country, sector, theme, policy, and even global levels. As the development community recognizes the importance of not only a comprehensive but also a coordinated approach to developing country challenges and emphasizes partnerships, development evaluators are increasingly engaged in joint evaluations. These joint evaluations, while advantageous in many respects, add to the complexity of development evaluation (OECD 2006). Additionally, development evaluators increasingly face the measurement challenge of determining the performance of an individual development organization in this broader context and of identifying its contribution. This text is intended as a tool for use in building development evaluation capacity. It aims to help development evaluators think about and explore the new evaluation architecture and especially to design and conduct evaluations that focus on results in meeting the challenges of development.

Appropriate ICT as a Tool to Increase Effectiveness in ICT4D: Theoretical considerations and illustrating cases - Reijswoud, Victor van (The Electronic Journal of Information Systems in Developing Countries, 2009)
The need to bridge the digital divide is no longer a point of discussion and therefore focus has shifted to the design and implementation of programs that have the potential to close the information and knowledge gap between the developing and developed nations. Unfortunately, the majority of these programs are small and mimic what has been successful in the developed world. It has become increasingly clear that these successes do not necessarily translate well in the context of developing nations. This paper develops the hypothesis that Information and Communication Technology (ICT) projects in developing countries will become successful only when they are adapted to local conditions. The general concept of Appropriate Technology (AT) will be explored for the field of ICT. AT has already been embraced by fields like architecture, building technology and agriculture, but has not yet been rooted in ICT. The paper proposes a preliminary theory of Appropriate ICT along the lines of existing theories in AT and System development. The theory identifies Appropriate Technology principles at three levels: hardware, software and ICT change management. By means of real life mini cases in the ICT for Development context in Africa, the guiding principles for Appropriate ICT are illustrated. The paper will conclude with an agenda for further research in the three identified levels. The research agenda targets academia, governments, NGO's and industry.
Keywords: IMPORTANT